Comparing transfusion reaction risks for various plasma products – an analysis of 7 years of ISTARE haemovigilance data. (9th January 2018) - Saadah, Nicholas H.; van der Bom, Johanna G.; Wiersum‐Osselton, Johanna C.; Richardson, Clive; Middelburg, Rutger A.; Politis, Constantina; Renaudier, Philippe; Robillard, Pierre; Schipperus, Martin R.
Summary: Plasma transfusions may result in transfusion reactions. We used the International Surveillance of Transfusion‐Associated Reactions and Events (ISTARE) database, containing yearly reported national annual aggregate data on transfusion reactions from participating countries, to investigate risks of plasma transfusion reactions and compare transfusion reaction risks for different plasma types. We calculated risks for plasma transfusion reactions and compared transfusion reaction risks between plasma types using random effects regression on repeated measures. The ISTARE database contains data from 23 countries, reporting units issued and/or transfused and transfusion reactions observed for some portion of 7 years (2006–2012). Interquartile ranges (IQRs) of plasma transfusion reaction risks were: allergic reactions (5·6–72·2 reactions/10 5 units transfused); febrile non‐haemolytic transfusion reactions (0–9·1); transfusion‐associated circulatory overload (0–1·9); transfusion related acute lung injury (TRALI) (0–1·2); and hypotensive reactions (0–0·6). Apheresis plasma was associated with more allergic reactions [odds ratio (OR) = 1·29 (95% confidence interval: 1·19–1·40)] and hypotensive reactions [OR = 2·17 (1·38–3·41)] than whole blood‐derived plasma. Pathogen‐inactivated plasma was associated with fewer transfusion reactions than untreated plasma.